2010
DOI: 10.1111/j.1365-2591.2010.01819.x
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic accuracy of small volume cone beam computed tomography and intraoral periapical radiography for the detection of simulated external inflammatory root resorption

Abstract: CBCT is a reliable and valid method of detecting simulated EIR and performs significantly better than intraoral periapical radiography. Small volume CBCT operating with 360° of rotation of the X-ray source and detector is no better at detecting small, artificially created EIR cavities than the same device operating with 180° of rotation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
165
1
11

Year Published

2014
2014
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 191 publications
(179 citation statements)
references
References 42 publications
2
165
1
11
Order By: Relevance
“…After that, the full texts of the reserved 31 citations were obtained and evaluated per the inclusion criteria. Finally, 15 studies were included in the systematic review [17][18][19][20][21][22][23][24][25][26][27][28][29][30][31] ( Figure 1). Among the enrolled studies, nine studies reported the diagnos- tic efficacy of CBCT with a sample size of 1097 suspected ERR sites, and 11 reported information of PR with a sample size of 1072 sites (five studies focused on both modalities).…”
Section: Description Of Included Studiesmentioning
confidence: 99%
“…After that, the full texts of the reserved 31 citations were obtained and evaluated per the inclusion criteria. Finally, 15 studies were included in the systematic review [17][18][19][20][21][22][23][24][25][26][27][28][29][30][31] ( Figure 1). Among the enrolled studies, nine studies reported the diagnos- tic efficacy of CBCT with a sample size of 1097 suspected ERR sites, and 11 reported information of PR with a sample size of 1072 sites (five studies focused on both modalities).…”
Section: Description Of Included Studiesmentioning
confidence: 99%
“…2,3,4,5,6,16,17,18 However, the margins of the lesions artificially produced with drills in these studies are sharper than those of natural lesions, whose margins tend to be irregular. In the present study, simulated ERR was induced chemically because this procedure affords ill-defined margins that are similar to those with ERR of biological origin and clinical condition.…”
Section: Discussionmentioning
confidence: 63%
“…Poorly-standardized radiographs may result in a misinterpretation of disease onset or progression. This is particularly salient in the assessment of ERR, which can commence and progress rapidly (3). Even when customized bite blocks attached to the paralleling device are used to take serial radiographs, the images will never be identical (21).…”
Section: Temporal Perspectivesmentioning
confidence: 99%
“…Scans tended to be taken using the CBCT hardware's manufacturer's settings as was the case in the radiation dose study mentioned previously (27). Ex vivo evidence now exists to suggest that by altering the degree of rotation of the X-ray source and detector from 360° to 180° and therefore away from the manufacturer's settings, the effective dose to the patient is potentially halved without a reduction in diagnostic yield (3,29). Of further encouragement to the application of CBCT in Endodontics is the fact that these studies were examining the diagnostic accuracy of CBCT in the detection of the most common endodontic diseases, namely external root resorption (3) and apical periodontitis (29).…”
Section: Effective Dose Of Cbctmentioning
confidence: 99%
See 1 more Smart Citation